THE EFFECTIVE MESSAGE WITHIN THE HEALTH CAMPAIGN TO IMPROVE THE HEALTHY LIFE BEHAVIOUR - Hasan Basri (Proceeding International Conference on Information Technology and Business, 2016)
The result of thisresearch about the healthy behaviour changes of the cadres of Maternal Child Health Centre showed the effectivenessof the health campaign message from the local government of Bandar Lampung. There were the health behaviour changes with the quite significant result from the path analysis examined in the direct and indirect effect.It was concluded that the specific characteristics of the messageplayed an important role in the effectiveness of health campaigns. Moreover, the segmentation of the society also affected the effectiveness of the message. There were indications that the message received by the audience couldaffect the respondents’ healthy behaviour. This confirmed the basic assumption of Icek Ajzen’s theory of planned behaviour which became the theoretical basis of the research framework.KEYWORDS: Characteristics of The Message; Health Campaigns; Healthy Behaviour; Theory ofPlanned Behaviour